OLIY TA’LIM TIZIMI SIFATINI OSHIRISHDA ZAMONAVIY MENEJMENTNING O‘RNI VA AHAMIYATI - Davlatov Soibnazar Xo‘janiyazovich, (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
In this article, the use of management functions in improving the quality of the higher education system is studied, analyzed, and suggestions for ways to improve the quality of the higher education system are presented.